PERFIL TÉCNICO E SOCIOECONÔMICO DA AGRICULTURA DE SALVADOR DAS MISSÕES-RS - LIMA, ARLINDO J. P. D.; HENNIG, CRISTIANE D. C.; GROSSMANN, GILBERTO; BENETTI, JOÃO E. F. (Salão do Conhecimento, 2013)
Resumo